ANALISIS KETEPATAN KODING YANG DIHASILKAN KODER DI RSUD UNGARAN - Adhani Windari; Anton Kristijono (Poltekkes Kemenkes Semarang, 2016)
The results showed still found not exactly result of coding diagnoses and medical procedures resulting coder hospitalization. Coding accuracy percentage is only 74.67%, while inaccuracies coding reached 25.33%. Still found incompleteness of medical record documents, and in the way of documentation found there is no document name of the doctor, they discovered the graffiti and tippex. Posts diagnosis and medical procedures doctors are not entirely legible.Coder need training on a regular basis, both internal hospital or national scale and the need for more intensive socialization to medical personnel regarding the completeness and procedures for documenting medical records document.